The Effect of Board Tenure and CEO Duality on Firm Performance of Companies Listed in Nairobi’s Stock Exchange - Korir, Alfred; Cheruiyot, Thomas; Bii, Philip (European Journal of Business and Strategic Management, 2025)
Purpose: This study sought to investigate the effects of board tenure and CEO duality on firm performance among companies listed in Nairobi Stock Exchange from a time period of year 2014 to 2023. Methodology: The study was based on the Agency Theory of Jensen &Mackling (1976) emphasizing on managerial behavior in an organization. The study adopted a causal study design which was appropriate. The target population comprised of 65 listed firms in Nairobi Stock Exchange and a sample size of 41 firms, excluding financial and insurance firms as they are being regulated. Secondary data was collected from the audited annual financial reports and was analyzed by using both descriptive and inferential statistics. Findings: The study revealed that board tenure had significant effect on the performance of firms listed in Nairobi stock exchange. Where the board tenure (β 0.016), (P=0.000 had positive and significant relationship on firm performance. The study also revealed that CEO duality had a positive non-significant relation with firm performance (β 0.056), (P=0.25). Unique Contribution to Theory, Practice and Policy: The study recommended improvement of those corporate governance features which have positive impact on firm performance such as CEO Duality.